2014
DOI: 10.1186/1471-2458-14-493
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and the incidence of type 2 diabetes: a cohort study of Japanese male athletes

Abstract: BackgroundIn Japan, although the incidence of overweight (BMI ≥ 25) is still low compared with that in Europe and the United States, the prevalence of type 2 diabetes has increased over the last 15 years,. In both Japanese and Caucasian populations it has been reported that a high level of cardiorespiratory fitness protects against the development of type 2 diabetes. However, there are no reports focused specifically on athletes that investigate whether high cardiorespiratory fitness at a young age can prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Five cohort studies (seven publications) [23,50,77,78,[83][84][85] including 1273 cases and 38,870 participants were included in the analysis of cardiorespiratory fitness and type 2 diabetes risk. Two publications reported separately on men and women from the same study, Ref.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…Five cohort studies (seven publications) [23,50,77,78,[83][84][85] including 1273 cases and 38,870 participants were included in the analysis of cardiorespiratory fitness and type 2 diabetes risk. Two publications reported separately on men and women from the same study, Ref.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…Juntendo University alumni study (2014) 24) . This study involved a follow-up of graduates from Juntendo University.…”
Section: Tgs (2010-2) 23)mentioning
confidence: 99%
“…Thus, it is also possible that muscle strength in middle age men is a good marker for the prediction of T2DM, but not at a young age. Nonetheless, our data showed that Japanese male athletes with high cardiorespiratory fitness during their college years are at low risk for future T2DM 11) , similar to the general population 20) .…”
Section: Discussionmentioning
confidence: 51%
“…The Physical Education School of Juntendo University Alumni Cohort Study included subjects engaged in college sports clubs such as track and field, gymnastics, soccer, and judo, and who participated in training for competitions in their respective sport 11) . Most of the study subjects were competitive athletes at least while attending the college.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation